Design, testing, commissioning, and early operation of the third-generation n_TOF neutron spallation target at CERN - Esposito Raffaele; Calviani Marco; Aberle Oliver (EPJ Web of Conferences, 2023)
The n_TOF facility at the European Laboratory for Particle Physics (CERN) is a top-class, high-brightness neutron spallation source dedicated to high-resolution neutron time-of-flight experiments. During CERN’s Long Shutdown 2 (LS2, 2019-2021), the facility’s neutron spallation target was upgraded and is now operating with its third-generation target. The target is based on a pure-Pb core cooled by gaseous nitrogen and has been designed to withstand the impact of a 20-GeV/c proton beam in bunches of 1013 protons with a bunch duration of 6-8 ns RMS. The produced neutrons span 11 orders of magnitude in kinetic energy (from thermal to GeV) and are delivered to two experimental areas and a neutron irradiation station near the target. This contribution includes a description of the physics and engineering design processes that brought the facility from its second-generation target to its current third-generation target, the planned autopsy of the second-generation target in 2023 to investigate its status after 10 years of operation, tests under beam irradiation carried out on target prototypes at CERN’s HiRadMat facility, and the commissioning with beam of the new target, as well as the challenges encountered during the first year of its operation.